2022
DOI: 10.1177/26334895221096289
|View full text |Cite
|
Sign up to set email alerts
|

Applying the EPIS framework to policy-level considerations: Tobacco cessation policy implementation among California Medicaid managed care plans

Abstract: Background In 2016, the California Department of Healthcare Services (DHCS) released an “All Plan Letter” (APL 16-014) to its Medicaid managed care plans (MCPs) providing guidance on implementing tobacco-cessation coverage among Medicaid beneficiaries. However, implementation remains poor. We apply the Exploration, Preparation, Implementation, Sustainment (EPIS) framework to identify barriers and facilitators to fidelity to APL 16-014 across California Medicaid MCPs. Methods We assessed fidelity through semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Previous qualitative research suggests that bridging factors that contribute to APL implementation include the structure of compensation for physicians, not knowing about resources in the external environment, and external quality measures (Economou et al, 2022; Tam et al, 2022). Contracts between MCPs and physicians bridge the inner (MCP) and external (physicians) environments and can be structured in different ways to incentivize (fee‐for‐service) or disincentivize (capitation) delivery and documentation of tobacco‐dependence treatment (Economou et al, 2022). Dominant compensation type for providers (capitated payments/noncapitated payments) were obtained from the CAHP (California Association of Health Plans [CAHP], 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous qualitative research suggests that bridging factors that contribute to APL implementation include the structure of compensation for physicians, not knowing about resources in the external environment, and external quality measures (Economou et al, 2022; Tam et al, 2022). Contracts between MCPs and physicians bridge the inner (MCP) and external (physicians) environments and can be structured in different ways to incentivize (fee‐for‐service) or disincentivize (capitation) delivery and documentation of tobacco‐dependence treatment (Economou et al, 2022). Dominant compensation type for providers (capitated payments/noncapitated payments) were obtained from the CAHP (California Association of Health Plans [CAHP], 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has documented that only 5% of Medi-Cal MCPs have implemented all 20 different requirements detailed in the APL (McMenamin et al, 2020). Furthermore, two qualitative studies have been published that describe the barriers and facilitators to implementation of the APL within Medi-Cal MCPs and clinics (Economou et al, 2022;Tam et al, 2022). Economou et al (2022) reported that interviews with MCPs identified internal organizational resources (including human resources), technical infrastructure, incentives, educational and training resources from DHCS, and structure of contracts with providers as barriers to full implementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Exploration, Preparation, Implementation, and Sustainment (EPIS) framework is increasingly used to understand policy implementation failures in behavioral health [ 35 , 36 ]. A recent study [ 35 ] of four states’ experiences with implementing a complex evidence-based practice found that policy adoption (e.g., policymaker-mandated use) was insufficient for ensuring fidelity to the intervention despite sufficient funding for training and program reimbursement and the use of 29 different implementation strategies.…”
Section: Introductionmentioning
confidence: 99%